A review of reading motivation scales. Issue 2 (17th February 2018) - Davis, Marcia H.; Tonks, Stephen M.; Hock, Michael; Wang, Wenhao; Rodriguez, Aldo
Abstract : Reading motivation is a critical contributor to reading achievement and has the potential to influence its development. Educators, researchers, and evaluators need to select the best reading motivation scales for their research and classroom. The goals of this review were to identify a set of reading motivation student self-report scales used in research, examine the development and psychometric properties of each reading motivation scale, and compare scales on availability, reliability, age range, and motivation constructs measured. This article summarizes 16 current reading motivation scales. Findings suggest the need for more research regarding the multidimensionality of reading motivation and measures that could span early childhood to adolescence.